Perbedaan Tingkat Pengetahuan Kesehatan Gigi dan Mulut pada Guru dan Murid di Sekolah Dasar yang Memiliki UKGS dan Tanpa UKGS di Kabupaten Pangkep - Thioritz, Ernie; Asridiana; Septa, Badai; Adlinah Fatman, Siti; Mufakhirah (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2025)
Oral health is an important part of general health that affects quality of life. One of the government's efforts to improve the dental health of school-aged children is through the School Dental Health Program (UKGS). This study aims to determine the differences in oral health knowledge among teachers and students in elementary school with the UKGS program (SDN 24 Kalibone) and school without UKGS (SDN 25 Taraweang Kabba) in Pangkep Regency. This type of research is analytical observational with a cross-sectional approach. The study population was all teachers and fourth-grade students with a sample of 90 respondents using purposive sampling method. The research instrument was a questionnaire that has been tested for validity and reliability. The results showed that students in schools with  mostly had a good level of knowledge, while students in schools without UKGS were mostly in the fair category. Meanwhile, teachers both with and without UKGS were all in the good category, but teachers with UKGS had higher knowledge scores. Statistical tests showed a significant difference between the level of oral health knowledge of teachers and students with UKGS compared to those without UKGS. In conclusion, the UKGS program has proven to have a positive impact on increasing knowledge of dental and oral health among students and teachers.  Keywords : Dental; health; oral, knowledge; UKGS